Administrator and faculty perceptions of the general education program in colleges of agriculture - Ables, Higino A. (Education quarterly.)
The purpose of this study was to determine the perceptions of administrators and faculty regarding the general education program in the Bachelor of Science in Agriculture curriculum. This study made use of the administrators/faculty questionnaire 1-perceptions of the G.E. program. Data gathering was done by the authors and the research assistants of the Policy and Technical Advisory Group. The questionnaires were handcarried to the respondent colleges of agriculture and which were later returned by mail.